Validation of the energy resource assessment with experimental data for the site selection of a tidal turbine in the Tagus River estuary. (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Lisbon, the capital of Portugal, is located on the mouth of the Tagus River, where the current speedand direction are mainly governed by the local tides. The narrowest part of the river is located between Lisbon downtown and the western side of the city. This narrowing accelerates the water flow and makes it a potential site for a tidal energy system. A preliminary study based on numerical simulations using the software MOHID was conducted to assess potential energy yields throughout the estuary using freely available hindcast data. This allowed the selection of three potential sites for a tidal turbine in the Lisbon area based on yearly tidal and current energy density: off the coasts of Cacilhas, Bel´em, and Pa¸co de Arcos. However, even if the current model has been previously validated with experimental data, it was only done at two locations in the estuary that are far from the potentialsites. Due to the complexity of the phenomena driving the current speed at these locations, additional validation is necessary before committing to a specific site. This paper presents the numerical analysis, the experimental campaign and the validation of the results at those three locations. Drifters with sails of 3.4m and 4.5m depth were released at least 8 times at each location and retrieved after 15 minutes of free drift. Each drifter was tracked with a GPS and the current speed and direction were derived from the drifters’ trajectory. The analysis of the experimental data shows good agreement with the model, even though an error of 0.3m/s is consistent throughout the tests. This paper concludes with a discussion on the model temporal and spatial discretisation and the forces included in the analysis that could be the source of the differences between the numerical and experimental data.